Differentiation of Life-History Traits among Palmer Amaranth Populations (Amaranthus palmeri) and Its Relation to Cropping Systems and Glyphosate Sensitivity. Issue 3 (17th May 2017) - Bravo, Washington; Leon, Ramon G.; Ferrell, Jason A.; Mulvaney, Michael J.; Wood, C. Wesley
Abstract : Palmer amaranth's ability to evolve resistance to different herbicides has been studied extensively, but there is little information about how this weed species might be evolving other life-history traits that could potentially make it more aggressive and difficult to control. We characterized growth and morphological variation among 10 Palmer amaranth populations collected in Florida and Georgia from fields with different cropping histories, ranging from continuous short-statured crops (vegetables and peanut) to tall crops (corn and cotton) and from intensive herbicide use history to organic production. Palmer amaranth populations differed in multiple traits such as fresh and dry weight, days to flowering, plant height, and leaf and canopy shape. Differences between populations for these traits ranged from 36% up to 87%. Although glyphosate-resistant (GR) populations collected from cropping systems including GR crops exhibited higher values of the aforementioned variables than glyphosate-susceptible (GS) populations, variation in traits was not explained by glyphosate resistance or distance between populations. Cropping system components such as crop rotation and crop canopy structure better explained the differences among populations. The higher growth of GR populations compared with GS populations was likely the result of multiple selection forces present in the cropping systems in which they grow rather than a pleiotropic effect of the glyphosate resistance trait. Results suggest that Palmer amaranth can evolve life-history traits increasing its growth and reproduction potential in cropping systems, which explains its rapid spread throughout the United States. Furthermore, our findings highlight the need to consider the evolutionary consequences of crop rotation structure and the use of more competitive crops, which might promote the selection of more aggressive biotypes in weed species with high genetic variability.